2013
DOI: 10.1038/ismej.2013.195
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhizal fungi contribute to soil organic matter cycling in sub-boreal forests

Abstract: Soils of northern temperate and boreal forests represent a large terrestrial carbon (C) sink. The fate of this C under elevated atmospheric CO 2 and climate change is still uncertain. A fundamental knowledge gap is the extent to which ectomycorrhizal fungi (EMF) and saprotrophic fungi contribute to C cycling in the systems by soil organic matter (SOM) decomposition. In this study, we used a novel approach to generate and compare enzymatically active EMF hyphae-dominated and saprotrophic hyphae-enriched communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
70
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(85 citation statements)
references
References 104 publications
11
70
0
1
Order By: Relevance
“…Genera and species from different functional groups dominated at these stages of postfire forest development ( Fig. 4; see also Mycorrhizal fungi are crucial in SOM transformations (58)(59)(60). The ECM fungus Paxillus involutus can convert SOM using a mechanism similar to that employed by brown-rot fungi using Fenton chemistry (61).…”
Section: Discussionmentioning
confidence: 99%
“…Genera and species from different functional groups dominated at these stages of postfire forest development ( Fig. 4; see also Mycorrhizal fungi are crucial in SOM transformations (58)(59)(60). The ECM fungus Paxillus involutus can convert SOM using a mechanism similar to that employed by brown-rot fungi using Fenton chemistry (61).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that keeping the material confined in the mesh bags has prevented the displacement of the compost-borne community. Other researchers have used gammaradiation to sterilize the OM added to the mesh bags and and mineral horizons (on the right side) of control and fertilized plots at the Norway spruce forest (n = 3) obtained community composition with ECM and saprotrophic fungal abundances of 70% and less than 9% relative to the total fungal abundance, respectively (Phillips et al 2014). Nevertheless, it is important to bear in mind that the compost-borne fungi, which were present in mesh bags at both horizons and treatments, may or may not be adapted to the new conditions imposed in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to saprotrophic fungi, ectomycorrhizal (ECM) fungi constitute another major microbial group in boreal and northern temperate forests and may play an important role in OM decomposition. Unlike saprotrophs, ECM fungi forage the SOM to obtain nutrients such as N and P for the host plant and receive in return plant photosynthate C. Nevertheless, the ability of ECM fungi to produce oxidative enzymes suggests a potential role for these microbes in the decomposition of soil OM (Bödeker et al 2014;Phillips et al 2014). Furthermore, recent studies have shown that ECM fungi have retained similar oxidative capacity as saprotrophic fungi (Shah et al 2016).…”
mentioning
confidence: 99%
“…Although pine naturally exist in a relationship with ectomycorrhizal and saprotrophic fungi which significantly contribute to C cycling by SOM decomposition [56,57], here we focused only on bacteria from the perspective of microbial ecology, to obtain information on the structure and function of the microbial community members that were able to sustain in these humics-free basic conditions.…”
Section: Rhizospheric Microbiomementioning
confidence: 99%